Field Devices For Monitoring Soil Water Content - Rafael Muñoz-Carpena (EDIS)
In the context of water management for irrigation, measuring and monitoring soil water status is an essential component of best management practices (BMPs) to improve the sustainability of agriculture. This document is Bulletin 343, one of a series from the Department of Agricultrural and Biological Engineering, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First publihsed: July 2004. This document replaces in part CIR 532.